Hepatotoxic effect of chronic exposure of Tacrolimus in male Albino rats: Ali, I. Al-Ameedi1, Falah, M. K. Al-Rekabi1 and Ahmed,Sh. J.Al-Rikabi2 - Al-Ameedi, Ali, I. (The Iraqi Journal of Veterinary Medicine, 2016)
This study was carried out to investigate the hepatotoxicity of chronic adminstration of an immunosuppressant Tacrolimus in male albino rats. Thirty male albino rats were randomly divided into 3 equal groups, the first one (T1) recieved therapeutic dose (70µg/kg.BW) of Tacrolimus. The second group (T2) recieved double dose (140 µg/kg.BW) of Tacrolimus, while the third group recieved distilled water for the same period and considered as control (C). Alanine aminotransferase, Aspartate aminotransferases, Alkaline Phosphatase, serum potassium and serum calcium showed significant increase in both treated groups T1 and T2 as compared with control, proportional to the dose of Tacrolimus. There were histopathological changes seen in liver at the end of exposure manifested by necrosis, hemorrhage, hyperplasia and fibrosis.It can be concluded that Tacrolimus has hepatotoxic effects when used for a long period